The von Hippel–Lindau tumor suppressor gene product represses oncogenic β-catenin signaling in renal carcinoma cells - Peruzzi, Benedetta (National Academy of Sciences, 2006)
Loss of von Hippel–Lindau (VHL) tumor suppressor gene function occurs in familial and most sporadic clear cell renal cell carcinoma (RCC), resulting in the aberrant expression of genes that control cell proliferation, invasion, and angiogenesis. The molecular mechanisms by which VHL loss leads to tumorigenesis are not yet fully defined. VHL loss has been shown to allow robust RCC cell motility, invasiveness, and morphogenesis in response to hepatocyte growth factor (HGF) stimulation, processes that are known to contribute to tumor invasiveness and metastatic potential. Among the most likely intracellular mediators of these HGF-driven activities is β-catenin, a structural link between cadherens and the actin cytoskeleton, as well as a gene transactivator. We show that reconstitution of VHL expression in RCC cells repressed HGF-stimulated β-catenin tyrosyl phosphorylation, adherens junction disruption, cytoplasmic β-catenin accumulation, and reporter gene transactivation in RCC cells. Ectopic expression of a ubiquitination-resistant β-catenin mutant specifically restored HGF-stimulated invasion and morphogenesis in VHL-transfected RCC cells. VHL gene silencing in non-RCC renal epithelial cells phenotypically mimicked VHL loss in RCC, and HGF-driven invasiveness was blocked by the expression of a dominant-negative mutant of Tcf. We conclude that, unlike many other cancers, where HGF pathway activation contributes to malignancy through the acquisition of autocrine signaling, receptor overexpression, or mutation, in RCC cells VHL loss enables HGF-driven oncogenic β-catenin signaling. These findings identify β-catenin as a potential target in biomarker and drug development for RCC.